Analyzing efficiency measurement and influencing factors of China’s marine green economy: Based on a two-stage network DEA model - Zou, Wenjie; Yang, Yuping; Yang, Mengting; Zhang, Xiaoyan; Lai, Shennan; Chen, Huangxin (Frontiers in Marine Science, 2023)
This research adopts a two-stage network DEA model to measure marine green economy efficiency from 2006 to 2018 and employs the panel Tobit model to analyze the influencing factors. The results indicate that total efficiency and production efficiency of China’s marine green economy generally show a fluctuating downward trend. Further investigation of influencing factors shows that foreign direct investment and opening up have a significantly positive effect on total efficiency of the marine green economy, while industrial development level and marine economy development level have a negative effect on it. Additionally, these variables have varying impacts on different stages of the marine green economy. Our findings help identify the operational characteristics of the marine green economy at different stages and can assist policymakers in optimizing the development pattern of the marine economy.